The Socio-economic Development Efforts in the Post- war Northern Sri Lanka: A Review of the Secondary Data - Navaneethan, V.; Velnampy, T.; Nimalathasan, B. (University of Vavuniya, 2022)
In the fourteen years since the end of the war, the Northern province of Sri Lanka has made some progress toward post-war recovery. In the absence of a comprehensive post-war need assessment and strategic development plan for the province, this research intends to answer the question of to what extent the socio- economic development investments made by the government and international development partners impacted improving the socio-economic indicators of the Northern province. It is hoped that the paper will contribute to developing strategies for post-war development planning by summarizing the post-war socio- economic development achievements of Northern Sri Lanka. The economic development of Northern Sri Lanka in the post-war context is relatively slow due to the lack of productive infrastructure facilities, new technologies/skills, and poor marketing networks. Make sure the deployment of sufficient number of teachers and the human capital development is critical to improve the quality of education. The absence of men has forced women to take a more significant share of the domestic and income generation burden. It is important to empower the women with adequate educational opportunities, psychological support, social safety nets through which enable them to engage in sustainable local economic development initiatives. The investment made for health sector development for a region recovering from the devastations of the post- war is not adequate. Whilst the province made some progress in socio-economic development in the post- war era, the socio-economic conditions of Northern Sri Lanka need significant improvement to be on par with the national and international socio-economic benchmarks.
Keywords: Northern province; Post-War, Sri Lanka; Socio-economic development; JEL codes: Z13